Evaluation of tunica vaginalis flap-covering combined with modified Glenn–Anderson in one-stage repair of proximal hypospadias with incomplete penoscrotal transposition - Wang, Xin; Guan, Yong; Wu, Yong; Wang, Cong; Ma, Xiong; Zhang, Zhenhua; Zhang, Dongzheng (Frontiers in Pediatrics, 2022)
Objective: To explore the novel repair method for proximal hypospadias with incomplete penoscrotal transposition in children and evaluate the safe and effect. Methods: Retrospective analysis was conducted for the clinical data of 86 children with severe proximal hypospadias with incomplete penoscrotal transposition who hospitalized at our department from June, 2018 and February, 2021. 42 patients (group A) were repaired with value of tunica vaginalis flap cover combined modified Glenn-Anderson one-stage repair technique. And 44 patients (Group B) underwent two-step repair including value of tunica vaginalis flap covering Duplay technique and modified Glenn-Anderson technique. The parameters of operative duration, postoperative hospital stay, postoperative complications and costs were compared between 2 groups. Results: All operations were successful in both groups. No statistic difference in stenosis of meatus urinary (2.38% vs 4.54%, P=0.279), urethral stricture (2.38% vs 2.27%, P=0.948), urinary fistula (7.14% vs 6.82%, P=0.907) and urinary infection (7.14% vs 4.55%, P=0.309) between two groups. And there was no statistic difference in operation time (63.21±5.20 vs 62.07±4.47 min, P=0.059), postoperative off-bed time (7.02±1.32 vs 6.84±1.20 day, P=0.456) and hospitalization day (10.55±1.15 vs 10.15±1.45 day, P=0.092) between two groups. However, the Group B patients underwent second stage operation and extra costs. Three months after operation, the Group A’s PPPS (Shaft Skin and General Appearance scores) were higher judged by parents (Shaft Skin, 2.10±0.82vs1.93±0.62, p=0.024; General Appearance, 2.16±0.91vs1.93±0.72, p=0.042) and operator (Shaft Skin, 2.42±0.70vs2.25±0.58, p=0.025; General Appearance scores, 2.38±0.69vs2.29±0.51, p=0.041). Most parents and operators were satisfied with the appearance after one-stage repair. Conclusion: The advantages of the novel repair technique include one-stage operation with better appearance and less cost. And value of tunica vaginalis flap cover method is not only safe and effect but also a simpler method than conventional operation.